Haplotype analysis of the mitochondrial DNA d- loop region reveals the maternal origin and historical dynamics among the indigenous goat populations in east and west of the Democratic Republic of Congo - Simon, P.B.; Junga, J.O.; Mekuriaw, Getinet; Machuka, Eunice M.; Tiambo, Christian K.; Kabange, D.; Dieudinné, K.M.M.; Kizungu, R.V.; Ochieng, J.W.; Pelle, Roger (Wiley, 2022)
This study aimed at assessing haplotype diversity and population dynamics of three Congolese indigenous goat populations that included Kasai goat (KG), small goat (SG), and dwarf goat (DG) of the Democratic Republic of Congo (DRC). The 1169 bp d‐loop region of mitochondrial DNA (mtDNA) was sequenced for 339 Congolese indigenous goats. The total length of sequences was used to generate the haplotypes and evaluate their diversities, whereas the hypervariable region (HVI, 453 bp) was analyzed to define the maternal variation and the demographic dynamic. A total of 568 segregating sites that generated 192 haplotypes were observed from the entire d‐loop region (1169 bp d‐loop). Phylogenetic analyses using reference haplotypes from the six globally defined goat mtDNA haplogroups showed that all the three Congolese indigenous goat populations studied clustered into the dominant haplogroup A, as revealed by the neighbor‐joining (NJ) tree and median‐joining (MJ) network. Nine haplotypes were shared between the studied goats and goat populations from Pakistan (1 haplotype), Kenya, Ethiopia and Algeria (1 haplotype), Zimbabwe (1 haplotype), Cameroon (3 haplotypes), and Mozambique (3 haplotypes). The population pairwise analysis (FST) indicated a weak differentiation between the Congolese indigenous goat populations. Negative and significant (p‐value <.05) values for Fu's Fs (−20.418) and Tajima's (−2.189) tests showed the expansion in the history of the three Congolese indigenous goat populations. These results suggest a weak differentiation and a single maternal origin for the studied goats. This information will contribute to the improvement of the management strategies and long‐term conservation of indigenous goats in DRC.